Early childhood risk and protective factors and their association with adolescent sexual behaviors: A Latent Class Analysis - Qingyang Liu; Sara A. Vasilenko; Xiafei Wang; Rachel A. Razza (PLoS ONE, 2025)
Background Prior research examined associations between social-ecological risk and protective factors and adolescents’ sexual behaviors. However, scarce research explored how factors in early childhood impact adolescents’ sexual behavior. Methods In this study, we used a socioeconomically and racially diverse sample from the Future of Families and Child Wellbeing Study (N = 3,281; 51.3% male; 21.76% White, 50.1% Black, 24.61% Latinx) to uncover latent classes of early childhood social-ecological risk and protective factors, examine the demographic characteristics of each latent class, and examine how these classes are associated with adolescents’ sexual behaviors. Results Four latent classes were identified: Multidimensional Protective (21.5%), Socioeconomic Status Risk (59.2%), Neighborhood Risk (7.3%), and Low Father Education (12%). Compared to the Multidimensional Protective class, adolescents in the Socioeconomic Status Risk class had a higher prevalence of sexual initiation, early sexual initiation, sex without a condom at first intercourse, and multiple sexual partners. Adolescents in the Socioeconomic Status Risk class had a higher prevalence of having sex without a condom at first intercourse than those in the Neighborhood Risk class. Adolescents in the Low Father Education class had a higher prevalence of having multiple sexual partners than those in the Multidimensional Protective class. Conclusion These findings suggest the need for early, targeted interventions, such as parenting support programs, father engagement initiatives, and community-based efforts to strengthen neighborhood cohesion, to promote long-term sexual health during adolescence.